Analisis Kemampuan Koneksi Matematika dalam Pemecahan Masalah Segitiga - Timbul Yuwono; Everista Gema Londar; Vivi Suwanti (Department of Mathematics Education, Faculty of Tarbiyah and Teacher Training, UIN Sunan Ampel Surabaya, 2020)
This study aims to describe the mathematical connection ability of students in the high, medium, and low categories in solving math problems based on Polya's steps. This study used a qualitative approach with descriptive methods carried out in class VII SMP PGRI 06 Malang in the 2019/2020 academic year. The subjects of this study were 22 students of which three students' categorized into high mathematical connection ability, four students categorized into medium mathematical connection ability, and fifteen students categorized into low mathematical connection ability. The results of this study show that students with the high category of mathematical connection ability were able to connect between concepts by making concept maps and solving problems well. Students with the medium group of mathematical connection ability can connect between concept, but in the episode of implementing the plan and looking back at the results of their work did not do well. Students with the low category of mathematical connection ability cannot connect between concepts, so they cannot understand the problem well and cannot plan problem-solving.